THE EFFECT OF PRODUCT QUALITY TOWARDS INTEREST IN BUYING â€œROTI KEMBUNGâ€ - hamdani, Nizar Alam; Fauziah, wulan (Universitas Pendidikan Indonesia, 2020)
The influence of Globalization and Modernization in the industry today has led to the rise of increasingly fierce and competitive business competition in the domestic and national markets. Quality products in culinary SMEs within the company are essential because, with no quality products, they will not be able to compete. This study tries to measure the level of interest in buying food